Hubungan Faktor Lingkungan dengan Kejadian Diare Balita di Wilayah Kerja Puskesmas Kambang Kecamatan Lengayang Kabupaten Pesisir Selatan Tahun 2013 - Fitra Dini; Rizanda Machmud; Roslaili Rasyid (Jurnal Kesehatan Andalas, 2015)
AbstrakPuskesmas Kambang adalah kejadian diare terbanyak di Pesisir Selatan yang menjadi insiden tertinggi di Sumatera Barat tahun 2012 dengan kondisi sanitasi yang sehat kurang dari 60%. Hampir sepertiga kasusnnya terjadi pada balita (26,7%). Tujuan penelitian adalah untuk mengetahui hubungan faktor lingkungan dengan kejadian diare balita. Penelitian menggunakan desain analitik cross sectional dengan jumlah subjek 63 orang dengan teknik multi stage random sampling. Penelitian menggunakan kuesioner melalui wawancara dan observasi. Hasil penelitian didapatkan analisis univariat kejadian diare balita 36 (57,1%), pembuangan tinja yang tidak sehat 34 (54%), sumber air minum tidak sehat 30 (47,6%), SPAL RT yang buruk 40 (63,5%), pengelolaan sampah yang buruk 36 (57,1%). Analisis bivariat didapatkan hasil ada hubungan signifikan antara pembuangan tinja dengan kejadian diare balita (p=0,010), OR=4,5. Ada hubungan signifikan antara sumber air minum dengan kejadian diare balita (p=0,026), OR=3,7. Ada hubungan yang signifikan antara SPAL RT dengan kejadian diare balita (p=0,003), OR=6. Ada hubungan yang signifikan antara pengelolaan sampah dengan kejadian diare balita (p=0,043), OR=3,3. Kesimpulan adalah ada hubungan yang signifikan antara faktor lingkungan.Kata kunci: diare, balita, faktor lingkungan AbstractKambang Health Center has the highest incidence of diarrhea in the South Pesisir which became the highest incidence in West Sumatra in 2012 with healthy sanitary conditions of less than 60%. Nearly one-third of cases occur in children under five (26.7%). The objective of this study was to determine the relationship of environmental factors with the incidence of diarrhea in children under five.This study used a cross sectional analytic method with a total subjek were 63 people, chosen by multistage random sampling technique. This study also used a questionnaire with interviewed and observation. Univariate analysis results showed that the incidence of diarrhea children under five 36 (57.1%), unsanitary excreta disposal 34 (54%), the source of drinking water is not healthy 30 (47.6%), poor waste water drainage system 40 (63.5%), poor waste management 36 (57.1%). Bivariate analysis showed significant relationship between excreta disposal site with the incidence of diarrhea in children under five with p=0.010 and OR=4.5. There is a significant relationship between sources of drinking water with the incidence of diarrhea in children under five with p=0.026 and OR=3.7. There is a significant relationship between the waste water drainage system with the incidence of diarrhea in children under five with p=0.003 and OR=6. There is a significant relationship between waste management with the incidence of diarrhea in children under five with p=0.043 and OR=3.3.In conclusion, there were significant relationship between environmental factors.Keywords: diarrhea, children under five, environmental factors